Social stigma towards nurses taking care of patients with COVID-19 in Indonesia: A mixed-methods study - Marisa Junianti Manik; Siska Natalia; Theresia Theresia (Belitung Raya Foundation, Indonesia, 2021)
Background: The condition of the Indonesians’ unpreparedness for the COVID-19 pandemic has caused anxiety and fear. The public’s fears of COVID-19 cases have led to a negative stigma. As part of health workers in disaster management’s main pillars in health services, nurses are most vulnerable to infection and not free from the stigma. Objective: This study aimed to describe the social stigma against nurses taking care of patients with COVID-19 and experiencing suspected or probable or confirmed COVID-19 cases in Indonesia. Methods: This study was a mixed-method study using a sequential explanatory design-participant selection model. The selection of respondents used the convenience sampling technique. The number of respondents in the quantitative stage was 118 respondents. For qualitative data, selected participants were respondents with a stigma score of more than 21 nurses and willing to continue the interview process. There were 11 participants in the qualitative stage. This study used the modified Stigma Scale of the Explanatory Model Interview Catalog for quantitative data and four semi-structured questions to obtain qualitative data. Quantitative data were processed in descriptive statistics, and a thematic analysis was performed to analyze the qualitative data. Results: The highest stigma score of 118 respondents was 37, and the lowest score was zero. The stigma score had a mean of 12.28 (SD ± 7.9). The higher the score obtained leads to a higher level of stigma received. From a total of 11 participants interviewed, four main themes emerged: rejection, feeling down and afraid, sources of support, and professional vigilance. Conclusion: The social stigma experienced by nurses comes from colleagues and society and impacts psychological distress. Support from families and colleagues strengthens nurses in facing social stigma. Nevertheless, nurses uphold the values to remain grateful and carry out professional responsibilities in taking care of patients. Nurses should be provided with psychological support and be prepared for disasters to provide excellent health services and reduce adverse mental health.